2005
DOI: 10.1002/rcm.2185
|View full text |Cite
|
Sign up to set email alerts
|

Identification and mass spectrometric characterization of glycosylated flavonoids in Triticum durum plants by high‐performance liquid chromatography with tandem mass spectrometry

Abstract: A mass spectrometric method for extensive detection and semi-quantitative determination of flavonoid glycosides in stem and leaves of young Triticum durum plants is presented. About 100 g of sample were lyophilized and ground, and the compounds of interest were then extracted, cleaned-up, and fractionated using high-performance liquid chromatography (HPLC). Tandem mass spectrometry analyses were performed using a quadrupole-linear ion trap instrument with an information-dependent data acquisition (IDA) protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 39 publications
5
83
0
1
Order By: Relevance
“…5C). In rice and wheat seedlings, tricin derivatives have been detected almost exclusively as O-glycosides (Cavaliere et al, 2005;Brazier-Hicks et al, 2009). Thus, our data strongly indicated that a completely different enzyme system is involved in flavone O-glycoside biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5C). In rice and wheat seedlings, tricin derivatives have been detected almost exclusively as O-glycosides (Cavaliere et al, 2005;Brazier-Hicks et al, 2009). Thus, our data strongly indicated that a completely different enzyme system is involved in flavone O-glycoside biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that tricin and isovitexin derivatives are the major flavonoids in vegetative tissues of rice (Shih et al, 2008). Both tricin and isovitexin are frequently O-glycosylated (Cavaliere et al, 2005), and the aglycones can be released by acid treatment. In the acid-hydrolyzed methanolic extracts of CYP93G2 mutant leaves, the levels of tricin detected were comparable to those of wild-type samples (Fig.…”
Section: Rice Cyp93g2 T-dna Insertion Mutants Are Depleted In C-glycomentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we suggest that the ion at m/z 1278 arise by addition of a glucose residue of m/z 150 from the ion at m/z 1128 (complex E), fragment that comes from the neutral reaction between D (m/z 1072) and another iron ion (+56 Da) (Cavaliere et al, 2005;Satterfield & Brodbelt, 2001). …”
Section: Journal Of Agricultural Studiesmentioning
confidence: 91%
“…Various plants produce a wide variety of C-glycosyl flavonoids in the leaves, however the parts of such plants traditionally present in the human diet appear to contain a narrower range. In durum wheat (Triticum durum) for example, 29 C-glycosyl derivatives of apigenin, luteolin and chrysoeriol, including some di-C-glycosides, have been identified in the leaves (Cavaliere et al, 2005). In contrast, wheat grain is known to contain only 5 such compounds, 4 of which are derivatives of the flavone luteolin.…”
Section: Introduction: C-glycosylation Of Flavonoidsmentioning
confidence: 99%